Macromedia Dreamweaver MX 2004 unleashed - Ruvalcaba, Zak (Sams, 2005)
As an experienced Macromedia Dreamweaver user, you know that it is a powerful web development tool, but you're lacking the knowledge to fully exploit the potential of the Dreamweaver environment. As a skilled website developer and programmer, you have that knowledge, but you're lacking the experience with the Dreamweaver program. Either way, Macromedia Dreamweaver MX 2004 Unleashed is what you need. The most complete guide to cover Dreamweaver MX 2004's powerful features, it will show you strategies for designing, managing and developing sophisticated websites within the Dreamweaver environment. It will also guide you through the realm of dynamic sites, which will ultimately enable a richer experience for the end user. These techniques are not covered in other intermediate-level Dreamweaver books. Let Unleashed help you unleash the potential of your Dreamweaver MX 2004 websites.